Profitability and Major Problems of Coffee Production in Palpa District, Nepal - Acharya, Bibek; Dhakal, Shiva C. (International Journal of Applied Sciences and Biotechnology, 2014)
The survey was conducted in Palpa district of Nepal in 2013 to assess the profitability and major problems associated with coffee production. Barangdi, Boughapokharathok, Madanpokhara and Khaseauli Village development committees (VDCs) were selected for the survey. A household survey of 110 coffee growers was conducted. Primary data were collected through face to face interview, direct observation; secondary data were collected from different publications. Data was analysed by using SPSS V16, Microsoft Excel and STATA 12. It was found that the coffee contributes about 10 percent to the annual household income. The GM was found NRs. 6637.52 and net profit of NRs. 4783.52 per ropani and the profitability index of 1.47 shows the coffee business as profitable business. The major problems in the coffee production were the high insect pest attack such as red and white borer. About 63 percentage respondents had said that the insect pest (white borer) was the major problem followed by low market price of the fresh cherry. It shows that the coffee business may be the suitable and financially feasible business in the mid hills of Nepal and need to address the major problems associated in production. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11252 Int J Appl Sci Biotechnol, Vol. 2(4): 460-463